Revolution - Wiles, Deborah (Wiles, Deborah. Sixties trilogy, 2014)
It's 1964 in Greenwood, Mississippi, and Sunny's town is being invaded by people from up north who are coming to help people register to vote. Her personal life isn't much better, as a new stepmother, brother, and sister are crowding into her life, giving her little room to breathe.--From publisher description.